2016
DOI: 10.3892/ijmm.2016.2508
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus-mediated PHLDA2 overexpression inhibits trophoblast proliferation, migration and invasion, and induces apoptosis

Abstract: Inadequate trophoblast invasion and increased trophoblast apoptosis cause serious pregnancy complications. Pleckstrin homology-like domain, family A, member 2 (PHLDA2) has been linked to fetal size at birth and growth restriction in a number of studies. However, the impact of PHLDA2 on trophoblast function had not been studied previously, to the best of our knowledge. In the present study, immunofluorescence staining demonstrated that primary trophoblasts isolated from placental villous tissues were positive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
0
8
0
2
Order By: Relevance
“…Previous studies have suggested that is a growth suppressor gene and that overexpression of this gene in the placenta leads to growth restricted pregnancies both in humans and in animal models (Jensen et al, 2014). Furthermore, ectopic expression of PHLDA2 results in pregnancy complications possibly by promoting apoptosis and suppressing trophoblast growth (Jin et al, 2016). In cancer, the role of PHLDA2 is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that is a growth suppressor gene and that overexpression of this gene in the placenta leads to growth restricted pregnancies both in humans and in animal models (Jensen et al, 2014). Furthermore, ectopic expression of PHLDA2 results in pregnancy complications possibly by promoting apoptosis and suppressing trophoblast growth (Jin et al, 2016). In cancer, the role of PHLDA2 is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Lentiviruses were also generated in Shanghai Taitool Bioscience Co., Ltd. (China). For TBX3 knockdown experiment, lentivirus transduction at a multiplicity of infection (MOI) of 10 was accomplished according to previous studies [50, 51]. Transfected Cells were treated with the addition of 2 μg/mL puromycin (Gibco, Grand Island, NY, A1113803) for 2 to 3 passages, and cells stably expressing GFP were used for subsequent analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Lentiviruses were also generated in Shanghai Taitool Bioscience Co., Ltd. (China). For TBX3 knockdown experiment, lentivirus transduction at a multiplicity of infection (MOI) of 10 was accomplished according to previous studies [36, 37]. Transfected Cells were treated with the addition of 2μg/mL puromycin (Gibco, A1113803) for 2-3 passages and cells stably expressing GFP were used for subsequent analyses.…”
Section: Methodsmentioning
confidence: 99%